Epicardial Contribution to the Developing and Injured Heart: Exploring the Cellular Composition of the Epicardium - Streef, Thomas J.; Smits, Anke M. (Frontiers in Cardiovascular Medicine, 2021)
The epicardium is an essential cell population during cardiac development. It contributes different cell types to the developing heart through epithelial-to-mesenchymal transition (EMT) and it secretes paracrine factors that support cardiac tissue formation. In the adult heart the epicardium is a quiescent layer of cells which can be reactivated upon ischemic injury, initiating an embryonic-like response in the epicardium that contributes to post-injury repair processes. Therefore, the epicardial layer is considered an interesting target population to stimulate endogenous repair mechanisms. To date it is still not clear whether there are distinct cell populations in the epicardium that contribute to specific lineages or aid in cardiac repair, or that the epicardium functions as a whole. To address this putative heterogeneity, novel techniques such as single cell RNA sequencing (scRNA seq) are being applied. In this review, we summarize the role of the epicardium during development and after injury and provide an overview of the most recent insights into the cellular composition and diversity of the epicardium.